Radiotherapy response in head and neck cancer – evaluation of the primary tumour site. (June 2014) - Sjövall, Johanna; Brun, Eva; Almquist, Helen; Kjellén, Elisabeth; Wahlberg, Peter
Abstract Conclusion: PET-CT scans seem to be sufficient to rule out residual tumour at the primary site. Patients with positive or equivocal PET findings should be scheduled for endoscopy with biopsy or a second PET-CT scan. Objectives: Assessment of remission at the primary site, in patients treated with organ preservation therapy with curative intent, is important to identify residual tumours requiring treatment with salvage surgery. The aim of this study was to evaluate the diagnostic accuracy of fluorodeoxyglucose positron emission tomography (FDG-PET) after radiotherapy with or without chemotherapy in assessing primary site response in patients with head and neck cancer. Methods: A total of 82 patients, with a positive baseline PET-CT scan before start of treatment, were evaluated with a PET-CT scan 6–7 weeks post-radiotherapy and with a clinical examination/endoscopy with or without biopsy 1–2 weeks later. The majority of patients had p16-positive oropharyngeal tumours. Results: Post-treatment, 77% of the patients had no visible hypermetabolism. If equivocal PET scans are regarded as positive, the sensitivity, specificity, negative (NPV) and positive predictive value (PPV) and accuracy were 100%, 78%, 100%, 6% and 78%, respectively. Eight patients suffered from relapses involving the primary site during the 9-month follow-up.